ผลกระทบของการออกใบสำคัญแสดงสิทธิ์การซื้อหุ้นต่อมูลค่าของผู้ถือหุ้นสามัญ : การศึกษาจากตลาดหลักทรัพย์แห่งประเทศไทย - ไชยา ศรีสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This thesis employs the event study methodology to study the effect of warrant issued on shareholder s wealth. The data is the stock return from the Stock Exchange of Thailand during 1995 to 2002. It is found that the issuance of warrant affects the change in underlying stock s return significantly. However, such effect is seemed to be the overshooting. The study shows the decreasing of the stock s return a few days later. It can be argued that the investment substitution ws the case. Some investor may switch his/her investment from the underlying stock to the warrant. This switching may be explained as the result from additional information of both risk factor and liquidity factor. Sequence of warrant issuance is not significantly relevant to any effect. Further studies were recommended to study more regarding wealth redistribution effect from warrant issued.